Early-stage intestinal-type gastric adenocarcinoma as an incidental finding: case report and review of literature - Mauricio, Leonel Iturbide; Leal , Hector Garza; Lòpez, Jesùs Renè Tadeo Calleja; Morales , Genaro Arguelles; Silva, Jonathan Ricardo; Ordaz , David Torres (International Journal of Research in Medical Sciences, 2023)
Gastric cancer is the malignant neoplasm in which gastric resection is the only viable strategy for long-term survival. Gastric carcinoma typically does not produce symptoms, therefore presenting as either advance or metastatic disease at the time of diagnosis. The most common early symptoms tend to be abdominal pain and weight loss. Adequate surgical resection is the only curative therapeutic option in patients with resectable gastric cancer. We present the case of a 66-year-old male patient who initially presented with abdominal pain and one episode of gastrointestinal bleeding, for which an endoscopic biopsy was conducted which reported intestinal-type gastric adenocarcinoma. Subtotal gastrectomy with Billroth II anastomosis was then performed without reported complications. Patient remains asymptomatic 3 months following the surgical intervention in surveillance with ambulatory care.